Multicentre study of multidisciplinary team assessment of pancreatic cancer resectability and treatment allocation. Issue 6 (4th March 2019) - Kirkegård, J; Aahlin, E K; Al-Saiddi, M; Bratlie, S O; Coolsen, M; de Haas, R J; den Dulk, M; Fristrup, C; Harrison, E M; Mortensen, M B; Nijkamp, M W; Persson, J; et al.
Abstract: Background: Multidisciplinary team (MDT) meetings have been adopted widely to ensure optimal treatment for patients with cancer. Agreements in tumour staging, resectability assessments and treatment allocation between different MDTs were assessed. Methods: Of all patients referred to one hospital, 19 patients considered to have non-metastatic pancreatic cancer for evaluation were selected randomly for a multicentre study of MDT decisions in seven units across Northern Europe. Anonymized clinical information and radiological images were disseminated to the MDTs. All patients were reviewed by the MDTs for radiological T, N and M category, resectability assessment and treatment allocation. Each MDT was blinded to the decisions of other teams. Agreements were expressed as raw percentages and Krippendorff's α values, both with 95 per cent confidence intervals. Results: A total of 132 evaluations in 19 patients were carried out by the seven MDTs (1 evaluation was excluded owing to technical problems). The level of agreement for T, N and M categories ranged from moderate to near perfect (46·8, 61·1 and 82·8 per cent respectively), but there was substantial variation in assessment of resectability; seven patients were considered to be resectable by one MDT but unresectable by another. The MDTs all agreed on either a curative or palliative strategy in less than half of the patients (9 of 19). Only fair agreement in treatment allocation was observed (Krippendorff's α 0·31, 95 per cent c.i. 0·16 to 0·45). There was a high level of agreement in treatment allocation where resectability assessments were concordant. Conclusion: Considerable disparities in MDT evaluations of patients with pancreatic cancer exist, including substantial variation in resectability assessments. Graphical Abstract: There were large variations in resectability assessments among 19 patients evaluated at seven different multidisciplinary team boards. There was agreement on a curative or palliative approach in only nine patients. Not as concordant as expected